Seroepidemiology of pertussis in Hangzhou, China, during 2009-2017 - Yuyang Xu; Erping Xu; Shijun Liu; Wei Zheng; Xuechao Zhang; Jian Du; Xiaoping Zhang; Jun Wang; Xinren Che; Wenwen Gu; Yan Liu (Taylor & Francis Group, 2019)
Objective: To delineate seroepidemiology of pertussis in Hangzhou, to evaluate the protection levels of pertussis among healthy populations, for improving prevention strategy of pertussis.Methods: During 2009-2017, a multistage stratified random sampling method was employed to select participants included via physical examination for subjects in several Community Health Centers in Hangzhou. Enzyme-Linked Immunosorbent Assay (ELISA) was used to detect Immunoglobulin G (IgG) antibodies against pertussis in serum samples. Results were compared among 11 age groups. Univariate and multivariate analysis were used to analyze the associations among the rates of pertussis IgG seropositivity and the geometric mean concentration (GMC) levels of pertussis IgG and the related factors.Results: A total of 3360 subjects with available information were included, with 1745 male and 1615 female. Of these, 59.6% subjects had a clear immunization history of diphtheria-tetanus-pertussis vaccine (DTP). The vaccination rates of DTP had a declined trend with older age. The rate of pertussis IgG seropositivity was 69.9% (95% confidence interval: 68.3-71.5) and the GMC for pertussis IgG was 48.46 U/ml. Significantly higher seropositivity and GMC for pertussis IgG were found in subjects that had inoculation vaccine history or unknown history when compared those without inoculation of vaccine, lower in age groups <10, 20-29, and 30-39 y when compared to the other age groups evaluated.Conclusions: There are different distribution profiles both of the seropositivity and GMC for pertussis IgG for different age groups and immunization history of vaccine groups. In order to prevent pertussis occurrence, it is important to employ a booster dose of pertussis vaccine in adolescents and adults.